2022
DOI: 10.1016/j.chom.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Strong humoral immune responses against SARS-CoV-2 Spike after BNT162b2 mRNA vaccination with a 16-week interval between doses

Abstract: Highlights d One mRNA vaccine dose induces robust humoral responses in convalescent donors d An extended interval between doses leads to high humoral responses in naive donors d These responses are stronger than in naive donors vaccinated with a short interval d Vaccine-elicited antibodies decline more rapidly in naive than convalescent donors Authors

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 75 publications
9
105
0
Order By: Relevance
“…Overall, our results show that the SARS-CoV-2 Spike is abundantly expressed at the surface of infected human pAECs. This confirms that SARS-CoV-2-infected cells represent a potential A limitation of our study is the relatively low number of individuals analyzed; however, we note that our results that used authentic SARS-CoV-2-infected pAECs are consistent with the findings of many widely used serological assays [5,27]. Overall, our results show that the SARS-CoV-2 Spike is abundantly expressed at the surface of infected human pAECs.…”
Section: Recognition Of Sars-cov-2 Infected Paecs Correlates With Spike Recognition At the Surface Of 293t Cells Pseudoviral Neutralizatisupporting
confidence: 87%
See 2 more Smart Citations
“…Overall, our results show that the SARS-CoV-2 Spike is abundantly expressed at the surface of infected human pAECs. This confirms that SARS-CoV-2-infected cells represent a potential A limitation of our study is the relatively low number of individuals analyzed; however, we note that our results that used authentic SARS-CoV-2-infected pAECs are consistent with the findings of many widely used serological assays [5,27]. Overall, our results show that the SARS-CoV-2 Spike is abundantly expressed at the surface of infected human pAECs.…”
Section: Recognition Of Sars-cov-2 Infected Paecs Correlates With Spike Recognition At the Surface Of 293t Cells Pseudoviral Neutralizatisupporting
confidence: 87%
“…We then evaluated whether recognition of the Spike at the surface of the infected pAECs correlated with results generated via the serological assays normally used to study humoral responses in individuals who were infected/convalescent or vaccinated [5,27]. We observed that plasma recognition at the surface of infected (N+) cells significantly correlated with the binding of 293T cells expressing the full-length SARS-CoV-2 Spike (Figure 3A,D,G).…”
Section: Recognition Of Sars-cov-2 Infected Paecs Correlates With Spike Recognition At the Surface Of 293t Cells Pseudoviral Neutralizatimentioning
confidence: 92%
See 1 more Smart Citation
“…(2021) ) found that longer dosing intervals (6–14 weeks) resulted in stronger immune responses than the standard regimen (3–4 weeks) for Comirnaty. Tauzin etal. (2021) also support that a longer (16 weeks) interval induced more robust immune responses than a shorter interval (4 weeks) for Cominarty.…”
Section: Rationale Behind Delaying the Second Dosementioning
confidence: 99%
“…Our data suggests that the response to the first dose is ongoing, with new T cell clones still being generated, at the time of administration of the second dose in the current dosing schedules (3/4-weeks for Pfizer/Moderna vaccines). Increasing the spacing between the first and second doses might allow the response to the first dose to play out, before further immune stimulation and give better protection, several studies now suggest this 45,46 . Data from Canada and Great Britain also seem to suggest that increasing the spacing might give better protection 47 .…”
Section: Discussionmentioning
confidence: 99%